EKSISTENSI SASTRA LISAN MAMACA DI KABUPATEN PAMEKASAN, MADURA - Kusmayati, AM Hermien; Sayuti, Suminto A (LITERA, 2014)
This study aims to describe the existence and functions of the mamaca oral literature in Pamekasan Regency, Madura. The data source was the "Rukun Sampurna" mamaca oral literature community in Jalmak Village, Pamekasan, Madura. The data were collected through observations and interviews. They were analyzed by means of the emic and etic approaches. These two approaches were simultaneously employed to attain the objectivity of research findings. The findings are as follows. First, the mamaca oral community is developed by the "Rukun Sampurna" community through regular performances and fulfillment of the community's requests or invitations for special events. Second, the mamaca oral community stimulates the community to move to a better condition through the delivered messages. The audience will get inspiration for life spirit, optimism, enlightenment, and happiness.